Puerperal women’s knowledge of sudden death syndrome in babies and preventive measures - Pavlovski de Paula, Emily; Fadel, Cristina Berger; Lopes Lima, Melina; Alves, Fabiana Bucholdz Teixeira; Cabral, Luciane Patrícia Andreani; Krum, Everson Augusto (BIRTH AND GROWTH MEDICAL JOURNAL, 2022)
Introduction: Infant mortality is an important collective health data, as it is an indicator of the quality of care provided to mothers and children born alive in a certain territory. This study investigated the knowledge of puerperal women admitted to a public teaching hospital about sudden death syndrome in babies and its preventive measures, aiming to support the development of educational and preventive measures at hospital level. Material and methods: This was a quantitative-qualitative and descriptive study carried out in the context of a Multiprofessional Residency in Health program in urgency and emergency setting of a public teaching hospital in the countryside of Paraná, Brazil. The study sample consisted of all mediate puerperal women admitted to the maternity ward of the referred hospital from October to December 2019. Semi-structured interviews with an average duration of ten minutes were carried out using a semi-directed script based on the recommendations for prevention of sudden death of the Brazilian Society of Pediatrics. Results/discussion: A total of 61 puerperal women were included in the study, who showed little knowledge about sudden infant death syndrome and risky behaviors involved, such as positioning the baby on the side, using pillows, and sharing the bed with the baby. Ease of care, easier supervision, and physical and emotional comfort were the main reasons pointed out for bed sharing with the baby. Conclusion: It is of utmost importance to educate parents and family members on sudden infant death and on the adoption of simple and effective preventive measures.